Digital Public Relations on Instagram in Building Public Trust: A Content Analysis Study of the @damkarjogjaistimewa Account - Al Israh; Muhammad Najih Farihanto (Journal of Social Research, 2026)
Instagram has increasingly been utilized by public service institutions as a digital public relations platform to build and maintain public trust. This study aims to analyze digital public relations practices through Instagram in building public trust on the @damkarjogjaistimewa account. The research employs a qualitative approach using descriptive content analysis of Instagram posts representing institutional communication activities. Data were collected through non-participant observation of visual content and captions, which were then analyzed based on the theoretical framework of public trust encompassing competence, care, and integrity. The findings reveal that operational documentation content is the most dominant category compared to educational and informational content. This dominance indicates that the institution’s digital communication strategy emphasizes the visibility of real performance as the primary foundation for building public trust. Educational and informational content serves as supporting elements that strengthen communication through safety literacy and information transparency. This study concludes that digital public relations practices oriented toward performance representation, safety education, and transparent communication constitute an effective strategy for emergency service institutions in building public trust in the digital era.